Silicon: a beneficial nutrient for maize crop to enhance photochemical efficiency of photosystem II under salt stress. Issue 5 (16th April 2017) - Khan, Waqas–ud–Din; Aziz, Tariq; Hussain, Imran; Ramzani, Pia Muhammad Adnan; Reichenauer, Thomas G.
ABSTRACT: Soil salinity imposes an unprecedented risk to the soil fertility and availability of plant nutrients. The present proposal is designed to address the effect of salt stress on photosynthetic apparatus of maize including chlorophyll a fluorescence and how silicon nutrition helps to overcome this issue. In a sand culture experiment, two maize cultivars were sown in small pots with two levels of silicon (0 and 2 mM H2 SiO3 ) and two levels of salinity stress (0 and 60 mM NaCl). Salinity stress reduced dry matter yield and potassium (K) concentration in both maize cultivars and also induced inefficient working of photosynthetic apparatus including photochemical efficiency of photosystem II. Silicon addition alleviated NaCl stress on maize crop by improving the dry matter yield and water use efficiency (WUE). It decreased shoot Na concentration by increasing root and shoot K concentration of maize plants. It enhanced maximum quantum yield of primary photochemistry which leads to smooth electron transport chain. It also significantly enhanced shoot silicon concentration and has a significant positive correlation with WUE. Therefore, silicon-treated maize plants have better chance to survive under salt stress conditions as their photosynthetic apparatus is working far better than non-silicon-treated plants.